ISIS in Malaysia: a Case Study - Malik, Maszlee (2016)
According to the latest report produced by the Institute of Economics and Peace, Malaysia has emerged in the top 50, at the 49th spot on the Global Terrorism Index 2015. It has climbed 42 spots within three years from being 91st in 2012. The same report also revealed that Malaysia’s score 3.579 is on the lower scale of the index, in which zero denotes no impact of terrorism.1 Malaysia was also noted as among the top 17 source countries in the Organisation for Islamic Cooperation (OIC) that have seen its people ght for ISIS in Iraq and Syria. Since 2014, more than 100 ISIS-linked suspects have been detained by Malaysian government under the 2012 SOSMA act. While it was estimated that 123 Malaysians are now living in Iraq and Syria joining different fractions ghting in the war in Syria against Asad regime, while 66 of them have been identi ed to be af liated to the Islamic State of Iraq and Syria (ISIS).2 In October 2015, the total number of Isis-related arrests for the year 2015 has reached 36.